Reduced oxycodone brain delivery in rats due to lipopolysaccharide-induced inflammation: microdialysis insights into brain disposition and sex-specific pharmacokinetics - Frida Bällgren; Margareta Hammarlund-Udenaes; Irena Loryan (Fluids and Barriers of the CNS)
Abstract Background Oxycodone, a widely used opioid analgesic, has an unbound brain-to-plasma concentration ratio (Kp,uu) greater than unity, indicating active uptake across brain barriers associated with the putative proton-coupled organic cation (H+/OC) antiporter system. With this study, we aimed to elucidate oxycodone's CNS disposition during lipopolysaccharide (LPS)-induced systemic inflammation in Sprague–Dawley rats. Methods Using brain microdialysis, we dynamically and simultaneously monitored unbound oxycodone concentrations in blood, striatum, lateral ventricle, and cisterna magna following intravenous administration of oxycodone post-LPS challenge. Results Our results indicated a reduced, sex-independent brain net uptake of oxycodone across the blood–brain barrier (BBB) measured in the striatum. Notably, the LPS challenge has significantly altered the systemic pharmacokinetics (PK) of oxycodone, in a sex-specific manner, leading to lower clearance and higher blood concentrations in females compared to LPS-treated males and healthy rats of both sexes. Proteomic analysis using Olink Target 96 Mouse Exploratory assay confirmed the induction of systemic inflammation and neuroinflammation. The inflammation led to an increased paracellular transport, measured using 4 kDa dextran, while preserving net active uptake of oxycodone across both BBB and the blood-cerebrospinal fluid barrier (BCSFB), with Kp,uu values of 2.7 and 2.5, respectively. The extent of uptake was 1.6-fold lower (p < 0.0001) at the BBB and unchanged at the BCSFB after the LPS challenge compared to that in healthy rats. However, the mean exposure of unbound oxycodone in the brain following LPS was similar to that in healthy rats, primarily due to the LPS-induced changes in systemic exposure. Conclusions These findings highlight the dissimilar responses at blood–brain interfaces during LPS-induced inflammation. Advancing the knowledge of neuropharmacokinetic mechanisms, specifically those involving the H+/OC antiporter system, will enable the development of more effective therapeutic strategies during inflammation conditions. Graphical Abstract